Tree level hydrodynamic approach for resolving aboveground water storage and stomatal conductance and modeling the effects of tree hydraulic strategy. Issue 7 (8th July 2016) - Mirfenderesgi, Golnazalsadat; Bohrer, Gil; Matheny, Ashley M.; Fatichi, Simone; de Moraes Frasson, Renato Prata; Schäfer, Karina V. R.
Abstract: The finite difference ecosystem‐scale tree crown hydrodynamics model version 2 (FETCH2) is a tree‐scale hydrodynamic model of transpiration. The FETCH2 model employs a finite difference numerical methodology and a simplified single‐beam conduit system to explicitly resolve xylem water potentials throughout the vertical extent of a tree. Empirical equations relate water potential within the stem to stomatal conductance of the leaves at each height throughout the crown. While highly simplified, this approach brings additional realism to the simulation of transpiration by linking stomatal responses to stem water potential rather than directly to soil moisture, as is currently the case in the majority of land surface models. FETCH2 accounts for plant hydraulic traits, such as the degree of anisohydric/isohydric response of stomata, maximal xylem conductivity, vertical distribution of leaf area, and maximal and minimal xylem water content. We used FETCH2 along with sap flow and eddy covariance data sets collected from a mixed plot of two genera (oak/pine) in Silas Little Experimental Forest, NJ, USA, to conduct an analysis of the intergeneric variation of hydraulic strategies and their effects on diurnal and seasonal transpiration dynamics. We define these strategies through the parameters that describe the genus level transpiration and xylem conductivity responses to changes in stem water potential. Our evaluation revealed that FETCH2 considerably improved the simulation of ecosystem transpiration and latent heat flux in comparison to more conventional models. A virtual experiment showed that the model was able to capture the effect of hydraulic strategies such as isohydric/anisohydric behavior on stomatal conductance under different soil‐water availability conditions. Key Points: Linking stomatal response to stem water potential improves transpiration prediction FETCH2 simulates aboveground water storage, sap flux, and transpiration FETCH2 shows differences in isohydric/anisohydric behavior on stomatal conductance